Occurrence of pendelluft during ventilator weaning with T piece correlated with increased mortality in difficult-to-wean patients - Liu, Wanglin; Chi, Yi; Zhao, Yutong; He, Huaiwu; Long, Yun; Zhao, Zhanqi (Journal of intensive care, 2024)
Difficult-to-wean patients, typically identified as those failing the initial spontaneous breathing trial (SBT), face elevated mortality rates. Pendelluft, frequently observed in patients experiencing SBT failure, can be conveniently detected through bedside monitoring with electrical impedance tomography (EIT). This study aimed to explore the impact of pendelluft during SBT on difficult-to-wean patients. This retrospective observational study included difficult-to-wean patients undergoing spontaneous T piece breathing, during which EIT data were collected. Pendelluft occurrence was defined when its amplitude exceeded 2.5% of global tidal impedance variation. Physiological parameters during SBT were retrospectively retrieved from the EIT Examination Report Form. Other clinical data including mechanical ventilation duration, length of ICU stay, length of hospital stay, and 28-day mortality were retrieved from patient records in the hospital information system for each subject. Pendelluft was observed in 72 (70.4%) of the 108 included patients, with 16 (14.8%) experiencing mortality by day 28. The pendelluft group exhibited significantly higher mortality (19.7% vs. 3.1%, p = 0.035), longer median mechanical ventilation duration [9 (5-15) vs. 7 (5-11) days, p = 0.041] and shorter ventilator-free days at day 28 [18 (4-22) vs. 20 (16-23) days, p = 0.043]. The presence of pendellfut was independently associated with increased mortality at day 28 (OR = 10.50, 95% confidence interval   1.21-90.99, p = 0.033). Pendelluft occurred in 70.4% of difficult-to-wean patients undergoing T piece spontaneous breathing. Pendelluft was associated with worse clinical outcomes, including prolonged mechanical ventilation and increased mortality in this population. Our findings underscore the significance of monitoring pendelluft using EIT during SBT for difficult-to-wean patients.